Humanist Profit In The Perspective Values Pappasang Tau Toa Mangkasara - Depi, Sri; Said, Darwis; Damayanti, Ratna Ayu (Universitas Muhammadiyah Makassar, 2024)
This research aims to reveal the meaning of humanist profit from the perspective of pappapata tau toa mangkasara values. The informants in this research were 5 informants, consisting of 2 business informants, 1 official informant and 2 traditional figure informants. The research uses qualitative methods by using an ethnomethodological approach with data analysis techniques: (1) organizing data, (2) grouping based on categories, themes and answer patterns, (3) testing existing assumptions or problems with the data, (4) looking for alternative explanations share data. The results of the research show that by applying the four values of Mangkasara's papangkat tau toa, namely: (1) Sopanna ellu, (2) Madiri pangngea ri crew, (3) Sakbala na ri papangkat, (4) Sipakatau sipakainge humanist profits are created as follows; the first is to bring good luck (dalle), the second is to build good relationships or develop good relationships (dekkeng), the third is financial support in the form of money (doe), the fourth is to get opportunities or chances (kaangkat).